2017
DOI: 10.1371/journal.pbio.1002611
|View full text |Cite
|
Sign up to set email alerts
|

Object segmentation controls image reconstruction from natural scenes

Abstract: The structure of the physical world projects images onto our eyes. However, those images are often poorly representative of environmental structure: well-defined boundaries within the eye may correspond to irrelevant features of the physical world, while critical features of the physical world may be nearly invisible at the retinal projection. The challenge for the visual cortex is to sort these two types of features according to their utility in ultimately reconstructing percepts and interpreting the constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 105 publications
(204 reference statements)
3
46
1
Order By: Relevance
“…Two recent works showed that the orientationselective processing of Gabor patches sharpens under the influence of the higher-level representation of the natural scene in which it is inserted [33,34]. While Teufel and colleagues [33] suggest that such modulations stem from the high-level semantic interpretation of the image, Neri [34] interprets his findings as arising from mid-level stimulus analyses, as they were not modulated by manipulations hampering stimulus semantic interpretation. However, we need to be cautious while comparing our findings to those previous works.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Two recent works showed that the orientationselective processing of Gabor patches sharpens under the influence of the higher-level representation of the natural scene in which it is inserted [33,34]. While Teufel and colleagues [33] suggest that such modulations stem from the high-level semantic interpretation of the image, Neri [34] interprets his findings as arising from mid-level stimulus analyses, as they were not modulated by manipulations hampering stimulus semantic interpretation. However, we need to be cautious while comparing our findings to those previous works.…”
Section: Discussionmentioning
confidence: 96%
“…For example, access to a higher-level representation has been shown to boost or hamper the processing of basic attributes, depending on whether a stimulus is near or supra-threshold [60][61][62][63]. Two recent works showed that the orientationselective processing of Gabor patches sharpens under the influence of the higher-level representation of the natural scene in which it is inserted [33,34]. While Teufel and colleagues [33] suggest that such modulations stem from the high-level semantic interpretation of the image, Neri [34] interprets his findings as arising from mid-level stimulus analyses, as they were not modulated by manipulations hampering stimulus semantic interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations